Relationship between Microstructure Evolution and Tensile Properties of AlSi10Mg Alloys with Varying Mg Content and Solidification Cooling Rates - Maressa Gandolfi; Marcella Gautê Cavalcante Xavier; Leonardo Fernandes Gomes; Rodrigo André Valenzuela Reyes; Amauri Garcia; José Eduardo Spinelli (Metals, 2021)
This work explored and contrasted the effect of microstructure on the tensile properties of AlSi10Mg alloys generated by transient directional solidification depending on variations in cooling rate and magnesium (Mg) content (i.e., 0.45 and 1 wt.% Mg), with a focus on understanding the dendritic growth and phases constitution. Optical and scanning electron (SEM) microscopies, CALPHAD, and thermal analysis were used to describe the microstructure, forming phases, and resulting tensile properties. The findings showed that the experimental evolution of the primary dendritic spacing is very similar when both directionally solidified (DS) Al-10 wt.% Si-0.45 wt.% Mg and Al-10 wt.% Si-1 wt.% Mg alloys samples are compared. The secondary dendritic spacing was lower for the alloy with more Mg, especially considering the range of high growth velocities. Moreover, a greater fraction of (Al + Si + Mg2Si) ternary eutectic islands surrounding the α-Al dendritic matrix was noted for the alloy with 1 wt.% Mg. As a result of primary dendritic spacings greater than 180 μm related to lower cooling rates, slightly higher tensile properties were attained for the Al-10 wt.% Si-0.45 wt.% Mg alloy. In contrast, combining dendritic refining (<150 μm) and a larger Mg2Si fraction, fast-solidified DS Al-10 wt.% Si-1 wt.% Mg samples exhibited higher tensile strength and elongation. The control of cooling rate and fineness of the dendritic array provided a new insight related to the addition of Mg in slightly higher levels than conventional ones, capable of achieving a better balance of tensile properties in AlSi10Mg alloys.